Technology and the environment in the history of the economic thought. (10th July 2008) - Belloc, Marianna; D'Alessandro, Simone; Di Maio, Michele; Drago, Francesco; , Pietro Vertova
This paper explores the way the man?nature relationship and the related environmental problems have been dealt along with the history of the economic thought. We discuss a number of different theoretical frameworks (classical, Marxian and neoclassical economics, Georgescu-Roegen's approach and ecological economics) and organise the discussion around the following two crucial points: how the environment influences the economic activity and imposes constraints by means of the scarcity of natural resources; and how the human activity impacts the environment, according to the prevailing technology, and modifies the ecosystem. Throughout this examination, we stress from time to time the role technological progress is found to play according to the various paradigms analysed. Is technological progress always in contrast with environmental sustainability or it may be seen as a tool in the hands of the humankind to make development sustainable?